2017
DOI: 10.1002/adfm.201606584
|View full text |Cite
|
Sign up to set email alerts
|

Ions Matter: Description of the Anomalous Electronic Behavior in Methylammonium Lead Halide Perovskite Devices

Abstract: Carrier transport in methylammonium lead iodide (MAPbI 3 )-based hybrid organic-inorganic perovskites (HOIPs) is obscured by vacancy-mediated ion migration. Thus, the nature of migrating species (cation/anion) and their effect on electronic transport in MAPbI 3 has remained controversial. Temperature-dependent pulsed voltage-current measurements of MAPbI 3 thin films are performed under dark conditions, designed to decouple ion-migration/ accumulation and electronic transport. Measurement conditions (electric-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 46 publications
5
67
0
Order By: Relevance
“…88 Based on a bulk activation energy of 0.58 eV 88 , a rate of 733 hops per second would be expected at T = 300 K, with an associated diffusion coefficient of 10 −12 cm 2 s −1 . Effective activation energies as low as 0.1 eV have been reported experimentally, 92,93 which likely correspond to diffusion along extended defects (dislocations, grain boundaries, surfaces) 94,95 . The corresponding diffusion rate of 10 −5 cm 2 s −1 is very fast, but comparable to surface diffusion of iodine observed in other compounds.…”
Section: A Ion Migrationmentioning
confidence: 96%
“…88 Based on a bulk activation energy of 0.58 eV 88 , a rate of 733 hops per second would be expected at T = 300 K, with an associated diffusion coefficient of 10 −12 cm 2 s −1 . Effective activation energies as low as 0.1 eV have been reported experimentally, 92,93 which likely correspond to diffusion along extended defects (dislocations, grain boundaries, surfaces) 94,95 . The corresponding diffusion rate of 10 −5 cm 2 s −1 is very fast, but comparable to surface diffusion of iodine observed in other compounds.…”
Section: A Ion Migrationmentioning
confidence: 96%
“…Given that ion migration is a thermally activated process, the common approach to determine the activation energy experimentally is to conduct temperature dependent measurements such as impedance spectroscopy [50], ionic conductivity [77] transient current [78] and transient capacitance [79]. However, the activation energies obtained by different groups show a large discrepancy ranging from 0.1 to 1.0 eV.…”
Section: Ion Migrationmentioning
confidence: 99%
“…This anomalous hysteresis influences the power conversion efficiency of a PV device and occurs as a result of the large discrepancy between the forward and reverse scans. Recent studies have demonstrated that such I – V hysteresis can originate from ion migration, ferroelectricity, a photoinduced capacitive effect, and charge trapping/detrapping . Among these, ion migration and ferroelectricity are considered plausible origins of the I – V hysteresis .…”
Section: Introductionmentioning
confidence: 99%